Integration of Triz, morphological chart, and pugh matrix for redesigning ergonomics of car interior for the mobility-impaired - Suliano, Salami Bahariah (2021)
Individuals with disabilities in Malaysia are among the most vulnerable of the minority group in the Malaysian population. According to the World Health Organization (WHO), 15% of the world’s populations has some form of disability. According to Jabatan Kebajikan Masyarakat Malaysia (JKM), the number of registered disabled people is increasing, as recorded by their annual statistics. With a projected rise in the number, the number of referred groups that use the road also increases over time. Besides, they are the majority of those who have relied on private cars for their versatility. Adjustments and modifications in vehicle configuration are connected in some parts to the physical ailments frequently confronted by them. With incongruous design today in the market, disabled people faced difficulties to itinerant, as doing so contributed to the diminishing of physical and emotional impact on them. The objective of this research is to redesign an ergonomics interior of a car for the mobility-impaired using the Theory of Inventive Problem Solving (TRIZ), specifically function analysis, cause and effect analysis, and contradiction matrix. This redesign focuses on the driver’s area of a compact car drove by upper limb disabled drivers, lower limb disabled drivers, or combined limb disabled drivers. Analysis from a set of questionnaires was conducted to list down the most sought-after needs of the mobility-impaired person for satisfaction of their ergonomics. It was then followed by a hybrid of TRIZ, Morphological charts, and Pugh Matrix to direct the solution and choices of design for the redesign. Redesigned parts initiated with a verification study of ergonomics impact towards the manikin. The results of the questionnaire have identified eight not-ergonomics parts in percentage scored by respondents handle door (53.3%), handle headliner (53.3%), door (53.3%), upholstery back (53.3%), upholstery bottom (53.3%), steering (53.3%), gear knob (56.7%), and pedals (53.3%). Accordingly, the aforementioned parts are subjected to TRIZ solution method, which results in the eight proposed Inventive Principles. At the end of the study, a model of an ergonomically redesigned car interior for mobility impaired people was developed to address mobility and exclusion issues, allowing them to improve their daily activities. A simulation in CATIA on design verification comparing current design and redesigned parts show virtuous scores of 1 and 2 for RULA and within guidelines range for Biomechanics Single Action Analysis. The postquestionnaire results show that product redesign has a positive impact on the listed part. Therefore, this research demonstrated the necessity of redesigning car interior and improving ergonomic features extensively, specifically for limbdisabled drivers.